Solid State Bioconversion of Domestic Wastewater Treatment Plant Sludge into Compost by Screened Filamentous Fungi - Molla, Md. Abul Hossain (2002)
Similar to other countries, Malaysia is facing problems of safe and environmental friendly disposal of domestic wastewater treatment plant (DWTP) sludge. None of the conventional disposal techniques is recognized as safe and environmental friendly. Solid state bioconversion (SSB) is emerging as a natural promising environmental friendly process. This microbial-based technique of organic wastes bioremediation is gaining greater public acceptance. This study has exploited the SSB technique to rejuvenate the compo sting process as a remedy for safe disposal and reuse of the Indah Water Konsortium (lWK) DWPT sludge. In this study isolation, screening and selection of compatible mixed fungal culture from relevant sources were followed by optimization of the SSB process. The SSB of IWK DWTP sludge into compost was examined and the compost was tested for crop growth. Six fungal strains Phanerochaete chrysosporium 2094, RW-PI 512, Trichoderma harzianums, T. harzianumc, Aspergillus versicolor and Mucor hiemalis were identified as sludge acclimatized and non-phytopathogenic among 33 members. The T. harzianums with P. chrysosporium 2094 (TIP), and T. harzianums with M. hiemalis (TIM) were selected as the best compatible mixed fungal cultures. Four factors were optimized based on superior production of biomass, total organic carbon (TOC) and soluble protein (SP) for both mixed cultures of SSB of the IWK DWTP sludge. These were CIN ratio 30:1, wheat flour (WF) as a cheap carbon source, pH 4.5 to 5 . 5 and rice straw (RS) as a bulking material. Higher microbial growth was obtained in RS compared to sawdust (SD) in SSB of the IWK DWTP sludge based on measurement of optical density, soluble protein and glucosamine. Significantly the lowest CIN ratio of 12.14 for TIP and 12.58 for TIM were achieved using RS in composting bin at 75 days. The lowest germination index of 33.43% for TIP and 39.4% for TIM were attained at 30 days. Then it rose to around 90% at 60 days using RS in compo sting bin. The suitable electrical conductivity (EC dS/m) values of 0.33 for TIP and 0.35 for TIM in SD, 1.41 for TIP and 1.49 for TIM were attained in RS at 75 days. The above facts support the production of stabilized composts. Comparatively, superior composts were produced by TIP around 50-60 days of SSB. Compost could provide 50% N requirement of optimal dose of com production. Around 65 to 100% higher dry matter production was attained by 50% compost plus 50% N treatment compared to control. Heavy metals uptake were low; whereby the composts of the IWK DWTP sludge contained average 30 times lower than the USA standard limit. The SSB is potentially capable of natural friendly biodegradation of the IWK DWTP sludge into compost with significant reduction of moisture and volume, which have an excellent use for organic farming. It will open a new route of final safe disposal of the IWK DWTP sludge.